Multiple-Dose Pharmacokinetics, Pharmacodynamics, and Safety of the Urotensin-II Receptor Antagonist Palosuran in Healthy Male Subjects - Sidharta, Patricia N; van Giersbergen, Paul L M; Dingemanse, Jasper (Pharmacology, 2018)
To investigate the multiple-dose pharmacokinetics (PK), pharmacodynamics (PD), and tolerability of palosuran, a selective, potent antagonist of the human UT receptor. This was a double-blind, randomized, placebo-controlled study. Three dose levels were investigated for PKs, PDs, and safety in sequential groups of 8 subjects each. The plasma concentration-time profile is characterized by rapid absorption and 2 peaks after drug administration. The apparent terminal half-life was approximately 25 h. Steady-state concentrations were reached after 4-5 days of dosing. The accumulation factor was approximately 2.5. With increasing doses, a more than dose proportional increase in AUCτ and Cmax was observed. Urinary excretion of unchanged palosuran was below 3%. No consistent effect was found on any of the PD variables. Palosuran was well tolerated in multiple doses up to 500 mg b.i.d. Palosuran after multiple-dosing is a well-tolerated drug in healthy subjects, but this finding warrants further investigation in patients.